MODERN TECHNOLOGIES IN REHABILITATION OF CHILDREN AFTER SURGICAL CORRECTION OF CONGENITAL HEART DEFECTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Congenital heart defects (CHD) are one of the leading causes of childhood mortality and disability. Modern rehabilitation technologies are aimed at improving the quality of life of children after surgical treatment. This article discusses innovative approaches to recovery, including personalized rehabilitation programs, telemedicine and modern physiotherapeutic methods. Particular attention is paid to the organizational aspects of medical care and the role of an interdisciplinary approach in ensuring successful rehabilitation.